New Russian Legislative Approaches and Navigational Rights within the Northern Sea Route - Solski, Jan Jakub (The Yearbook of Polar Law Online, 2021)
The regulation of foreign navigation in the Northern Sea Route (NSR) has been dominated by the rules of international law applicable to merchant ships only. Neither the domestic set of rules of navigation on the NSR, based on Article 234 of UNCLOS nor the Polar Code applies to State-owned vessels. While the application of Article 234 has so far let Russia evade discussion on the navigational rights, one can expect an increasing spotlight on this issue. In response to the recent crossing of the NSR by a French warship, as well as the voices from the United States indicating similar plans, Russia has signalled the intention to adopt more stringent rules for passage of warships, potentially including the requirement of prior notification and pilotage. The aim of the paper is twofold. First, examine the navigational rights as applicable in the NSR. As such, the paper will discuss historical State practice and relevant international law to demonstrate, among other things, that the enclosure with straight baselines preserved innocent passage in all Russian Arctic straits. Second, examine the international legality of prior notification and pilotage in the context of the applicable navigational rights on the NSR.